2009
DOI: 10.1002/cncr.24253
|View full text |Cite
|
Sign up to set email alerts
|

Negative Helicobacter pylori status is associated with poor prognosis in patients with gastric cancer

Abstract: NELL‐1 (Nel‐like molecule‐1) is a secreted osteogenic growth factor first identified in human craniosynostosis (CS) patients. NELL‐1 protein has been observed to promote bone and cartilage differentiation and to suppress adipogenesis in both in vitro and in vivo models. Despite these findings, the cell surface receptors of NELL‐1 have remained unknown. In this study, we observed for the first time that NELL‐1 promotes cell adherence in multiple cell lines, including ST2, C3H10T1/2, M2‐10B4, ATDC5, and MC3T3 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
120
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(128 citation statements)
references
References 44 publications
7
120
1
Order By: Relevance
“…pylori infection may be localized in or around the tumour (classified as diffuse, localized, or none). 17 . An overall positivity rate of 72.0% was observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…pylori infection may be localized in or around the tumour (classified as diffuse, localized, or none). 17 . An overall positivity rate of 72.0% was observed in our patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients positive for H. pylori showed improved os and relapse-free survival. A prospective study by Marrelli et al 17 indicated that negative H. pylori status was an indicator of poor prognosis in patients with gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Marrelli et al [18] have reported that the vacA gene encodes the vacuolating cytokine VacA, which induces epithelial cell injury, and the degree of heterogeneity in vacA may be useful as a marker for peptic ulcer diseases.…”
Section: Frequencies Of Duodenal Ulcer and Gastric Cancermentioning
confidence: 99%